2021
DOI: 10.1088/2053-1591/ac3587
|View full text |Cite
|
Sign up to set email alerts
|

Evolution mechanism of cyclized structure of PAN-based pre-oxidized fiber during low temperature carbonization process

Abstract: The low temperature carbonization process is an important stage to realize the structural transition from the organic cyclized structure of PAN based pre-oxidized fiber to the inorganic pseudo-graphite structure of the ultimate carbon fiber. In the present paper, the evolution mechanism of cyclized structure and aggregation structure of PAN stabilized fiber during low temperature carbonization was studied by means of TGA, 13C-NMR, XRD, XPS and Raman. The results indicated that when the heat-treated temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For PAN, rapid shrinkage was observed in the temperature range of 300 to 400 °C. The molecular cyclization of PAN is typically reported to proceed below 400 °C, and carbonization through various mechanisms takes place around 400 to 600 °C. Therefore, in the calcination, the as-spun nanofibers, consisting of a mixture of Mo precursor and PAN, undergo thermal decomposition and carbonization to form C nanofibers structure. Subsequently, metal species nucleate within the C nanofibers, as reported in several studies on metal/C nanofibers. , …”
Section: Resultsmentioning
confidence: 99%
“…For PAN, rapid shrinkage was observed in the temperature range of 300 to 400 °C. The molecular cyclization of PAN is typically reported to proceed below 400 °C, and carbonization through various mechanisms takes place around 400 to 600 °C. Therefore, in the calcination, the as-spun nanofibers, consisting of a mixture of Mo precursor and PAN, undergo thermal decomposition and carbonization to form C nanofibers structure. Subsequently, metal species nucleate within the C nanofibers, as reported in several studies on metal/C nanofibers. , …”
Section: Resultsmentioning
confidence: 99%
“…Xue et al [15,16] reported that the pre-oxidation degree of PAN-based pre-oxidized fiber in the skin was higher, while it was the lowest in the core due to the decrease of oxygen content. The skin-core structure of pre-oxidized fibers could be weakened through the thermal treatment at a lower temperature for a long time, according to the work [17,18]. However, it was also easy to form the excessive oxygenated functional groups in the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Related investigations have revealed the chemical reaction mechanism and product structure during the preoxidation process can be obtained by means of infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR) and Raman spectra. Furthermore, the mechanisms of 'cyclization reaction', 'dehydrogenation reaction' and 'oxidation reaction' were proposed in the research [21][22][23], as well as the structural models of 'trapezoidal structure', 'aromatic heterocycle', 'imine crosslinking', 'polyene amine' and 'spread crosslinking' [24][25][26]. However, the effect mechanism of characteristic structure on the formation and evolution of embryonic conjugate structure has not been well established.…”
Section: Introductionmentioning
confidence: 99%